Dataset of PY53 Nickel-Titanate yellow pigments for plastic, enamel and ceramic glaze applications - Aslan, Emre; Toy, Emre; Guener, Zeynep; Yesilcic, Emine; Grijalbo, Alejandro; cicekc, Bugra (ELSEVIER, 2023)
This dataset shows the change in color tone in plastic (mas-terbatch), enamel, and ceramic (glaze) colored with PY53 Nickel-Titanate-Pigment calcined with different NiO ratios by solid-state reaction. The pigments were mixed with milled frits and applied to the metal and ceramic substance for enamel and ceramic glaze applications, respectively. For the plastic application, the pigments were mixed with melted polypropylene (PP) and formed into plastic plates. The CIELAB color space approach was used to assess L *, a *, b * val-ues over applications created for plastic, ceramic, and enamel trials. These data can be used to evaluate the color of PY53 Nickel-Titanate pigments with different NiO ratios in the ap-plications.(c) 2023 The Author(s). Published by Elsevier Inc. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/)
Keywords: Nickel-Titanate; Color tone; Plastic application; Enamel application; Ceramic application; NiO; Science & Technology - Other Topics